At sea vocal repertoire of a foraging seabird. (28th May 2019) - Thiebault, Andréa; Charrier, Isabelle; Pistorius, Pierre; Aubin, Thierry
Abstract : Seabirds spend most of their time at sea, yet our knowledge of their activities and behaviour is limited due to difficulties of in‐situ data collection. In particular, we know virtually nothing about their acoustic communication when at sea. We benefited from the recent development of miniaturised audio‐recording devices to deploy acoustic recorders on breeding Cape gannets Morus capensis to study their vocal activity while foraging. Call sequences were recorded on 1718 occasions, from which acoustic variables were measured on calls with good recording quality. A total of 1348 calls from 18 birds were measured in temporal and frequency domains. Each call was assigned to a behavioural context defined acoustically: sitting on the water, flying, taking off or just before diving. Potential discrimination among calls from different contexts was tested using the random forest algorithm. Within each context, individual stereotypy in the calls was assessed per acoustic variable using a measure of potential of individual coding, and as a combination of variables using a similar multivariate analysis. The acoustic structure differed according to the behavioural context (global accuracy of prediction 75%). Temporal variables (sequence and call duration) were most important to correctly classify the calls among the four contexts. When considering only two contexts, on the water and in the air (merging flying and diving), frequency and spectral variables (percentage of energy below 1200 Hz and fundamental frequency) were of most importance (accuracy 86%). A combination of acoustic variables was necessary to discriminate individuals, but calls from all contexts were not strongly individually distinct (accuracy 41–63%). We provided the first detailed acoustic analysis of a foraging seabird and demonstrated context‐specific acoustic structure in its vocalisations at sea. Our results suggest that seabirds use vocal communication to exchange various types of information that likely improves foraging success.